Development and validation of a questionnaire for table tennis teaching in physical education - Ortega-Zayas, Miguel Ángel; Cardona-Linares, Antonio José; Quílez, Alberto; García-Giménez, Alejandro; Lecina, Miguel; Pradas, Francisco (Frontiers in Psychology, 2025)
This study aimed to validate the “Racquet Sports Attitude Scale (RSAS)” questionnaire intended for the educational field. The RSAS is a Spanish instrument developed using the Delphi method and consists of 42 questions divided into five subsections benefits of table tennis (TT), facilitators for the application of TT, barriers to applying tennis table in physical education (PE), difficulties in applying the tennis table as a PE content and positive attitude toward racket sports), designed to evaluate the use and impact of the practice of the racket sports, in particular TT, among PE teachers. The semantic validation process involved a panel of experts (n = 16), followed by an evaluation carried out by a group of teachers from various secondary schools (n = 20). Three studies were conducted, the first of which was descriptive, comparative and correlational, to establish the data’s sociodemographic characteristics. The second was an exploratory factor analysis to confirm the number of dimensions of the questionnaire and its reliability and validity. The last study was a confirmatory factor analysis (to establish the final number of items and their structure. The ordinal alpha values ranged from 0.65 to 0.72, obtaining an average value of 0.70, indicating coherence between the measurement of the items. Chi-square values (X2 = 197.383; p < 0.001; CFI = 0.934; TLI = 0.923 and RMSEA = 0.030), showed that the original 5-factor model and 21 final items prevailed over the one-factor model, obtaining values >0.90. On the other hand, the validation results indicated that the factor structure of the RSAS scale was able to explain 46.72% of the variance (F1 = 13.93%; F2 = 10.97%; F3 = 8.57%; F4 = 6.85%; F5 = 6.38). It can be concluded that the structure of the RSAS is fully confirmed by the statistical analyses derived from the different models of structured equations and confirmatory factor analysis, suggesting that the validated model optimally addresses the data provided and contributes to the validation of the questionnaire under study.